This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have to solve the equation x 3 + 3 y 3 + 9 1 = x y , it's kinda hard to solve by factoring, and sometimes it's better to invoke some inequalities in an equality! By AM-GM, x 3 + 3 y 3 + 9 1 ≥ 3 ( 2 7 x 3 y 3 ) 3 1 = x y , thus, there is only one element which is ( x , y ) = ( 9 3 1 1 , 3 3 1 1 ) by setting x 3 = 3 y 3 = 9 1 which is the point where the function x 3 + 3 y 3 + 9 1 achieves its minimum value x y .